The Simple Additive Weighting(SAW) Method for Selecting Shrimp Types in a Microcontroller and SolarPanel-Based Shrimp Drying Control System - Ahmad Muhtadi; Ahmad Hudawi AS; Ahmad Khairi; Abdul Karim; Honainah; Tijaniyah (Jurnal JEETech, 2026)
This study applies the Simple Additive Weighting (SAW) method to select shrimp types in a microcontroller and solar panel-based shrimp drying control system. The aim is to enhance drying efficiency by determining the most suitable shrimp type based on multiple criteria, including moisture content, shrimp size, drying time, temperature, and humidity. The system uses sensors to monitor environmental conditions in real time and a microcontroller to automate the drying process, while solar panels provide a sustainable energy source. The SAW method evaluates each alternative by normalizing criteria values and calculating preference scores to produce a final ranking. the solar panel-based shrimp drying control system provides an efficient and sustainable solution for the drying process. By integrating sensors, a microcontroller, and automatic actuators, the system can maintain optimal temperature, humidity, and airflow. The electrical energy generated from the solar panel reaches a maximum of 90 within 5 hours. Based on the SAW method calculation, the highest value is obtained by rebon shrimp (Acetes Shrimp) as Alternative 5, with a score of 18.16. Meanwhile, the lowest humidity value measured by the sensor is 10.5% RH, indicating that the drying chamber has reached optimal conditions, allowing the shrimp to dry properly without spoilage